2013
DOI: 10.1073/pnas.1318268110
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of multiple system atrophy prions to transgenic mice

Abstract: Prions are proteins that adopt alternative conformations, which become self-propagating. Increasing evidence argues that prions feature in the synucleinopathies that include Parkinson's disease, Lewy body dementia, and multiple system atrophy (MSA). Although TgM83 +/+ mice homozygous for a mutant A53T α-synuclein transgene begin developing CNS dysfunction spontaneously at ∼10 mo of age, uninoculated TgM83 +/− mice (hemizygous for the transgene) remain healthy. To determine whether MSA brains contain α-synuclei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
416
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 396 publications
(452 citation statements)
references
References 49 publications
29
416
2
5
Order By: Relevance
“…In both cases, αS pathology is associated with a rapidly progressive motor phenotype that is subtly distinct from that in untreated, aged M83 Tg mice due to the initial foot drop presentation and the heightened neuroinflammatory response. From our findings, IM injections appear to induce a more rapid lethal motor phenotype (50-120 d incubation time) than reported in some studies where either homozygous or hemizygous M83 Tg were intracerebrally inoculated with CNS extracts from symptomatic M83 Tg (∼200 d incubation time) (23,24). However, Luk et al (21) reported that, in similar M83 Tg CNS extract transmission studies or with intracerebral injection of recombinant fib αS in homozygous M83 Tg mice, the incubation time to cause motor impairments was closer to what we observed resulting from IM injection of fib αS (i.e., ∼100 d) (21).…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…In both cases, αS pathology is associated with a rapidly progressive motor phenotype that is subtly distinct from that in untreated, aged M83 Tg mice due to the initial foot drop presentation and the heightened neuroinflammatory response. From our findings, IM injections appear to induce a more rapid lethal motor phenotype (50-120 d incubation time) than reported in some studies where either homozygous or hemizygous M83 Tg were intracerebrally inoculated with CNS extracts from symptomatic M83 Tg (∼200 d incubation time) (23,24). However, Luk et al (21) reported that, in similar M83 Tg CNS extract transmission studies or with intracerebral injection of recombinant fib αS in homozygous M83 Tg mice, the incubation time to cause motor impairments was closer to what we observed resulting from IM injection of fib αS (i.e., ∼100 d) (21).…”
Section: Discussionsupporting
confidence: 43%
“…Our ability to now synchronously and rapidly induce a motor phenotype and αS pathology by a peripheral injection of αS may prove invaluable in future studies exploring mechanisms of pathology induction and αS toxicity and may extend recent studies showing rapid induction following intracerebral inoculation (21)(22)(23)(24)(25)(26). Our finding that disease onset in M83 Tg mice can be shortened, predicted, and synchronized through a simple manipulation provides a valuable model to accelerate studies designed to fully understand the mechanisms underlying induction of the inclusion pathology and motor phenotype, but also to enable much more rapid and cost-effective preclinical testing of novel PD therapies.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…4 A and B). This coexistence distinguishes the hSOD1 D90A mice from previous disease models where the variation of strains is typically observed between individuals (1,34,35,41). Even so, the hSOD1 D90A mice highlight the notion that strain variation influences pathology, as previously observed for prions (27,28), and in patients and models for synucleopathies (33), Alzheimer's disease (1,35,36), and tauopathies (34).…”
Section: Discussionmentioning
confidence: 50%
“…These observations suggest that LBs serve as quality-control compartments that enable efficient digestion of toxic a-synuclein assemblies. Recent studies show that a-synuclein prionlike assemblies cause multiple system atrophy, which shares many features observed in PD (Watts et al 2013;Prusiner et al 2015).…”
Section: The Deposition Of Aggregates Is a Hallmark Of Neurodegeneratmentioning
confidence: 82%